Microstructural and mechanical behavior in dissimilar T91/T22 welded pipes. (2020) - Mittal, Rutash; Gupta, Ashutosh; Pratap, Karan; Shukla, Pratyush; Gupta, Shyam; Shanurrahman,
Abstract: The aim of this work is to investigate the microstructural and mechanical behavior of T91/T22 steel welded pipes with iron based filler material/wires using Gas Tungsten Arc Welding (GTAW) process. By the fusion of two metal across the weld joint a variety of microstructural variation is observed as a result of solidification and solid state transformation. So, the evaluation of this welded joint formed with filler wires of different composition is based on microhardness variation, Tensile strength of the welded specimen and the microstructural arrangements. The deformation of dissimilar welded joints depends on the base metals i.e. T91, T22 and on the composition of filler materials as proved my microhardness variation and tensile strength and microstructural variation. In the following experiment two different kind of specimen were prepared using two filler wires E91T1-G C and ER80S D2 as specimen E1 and E2. It has been observed that the tensile strength of Specimen E1(593 MPa) is higher than Specimen E2 (474 MPa) also the microhardness of Specimen E2 around the HAZ of T22 and weld metal is quite high due to which the brittleness of material there will increase and the material fails while tensile testing.